Transdermal Patch of Gnetum gnemon L. Leaf Extract as Drug Delivery System and Anti-Inflammatory Activity Agains Wistar Mice - Wijaya, Dina Permata; Amalia, Addienasyifa Nurul; Herlina, Herlina (Faculty of Mathematic and Natural Science, Garut University, 2026)
The melinjo leaf (Gnetum gnemon L.) is a plant of the Gnetaceae family that contains compounds including flavonoids, which have the potential to act as anti-inflammatories. Formulating melinjo leaf extract into a transdermal patch aims to deliver active compounds to the systemic circulation via the skin. The research aimed to develop a melinjo leaf extract into a transdermal patch its anti-inflammatory activity. The extraction of melinjo leaf using the maceration method with 70% ethanol. The transdermal patch containing melinjo leaf extract is formulated in three versions, each containing 20%, 25%, or 30% propylene glycol. The formulation was characterised by organoleptic, pH, moisture content, uniformity of thickness and weight, and elongation. The best formula is characterised by stability, uniformity of drug content, and anti-inflammatory activity in Wistar mice. The results indicated that transdermal application and oral administration of the melinjo leaf extract produced anti-inflammatory effects comparable to those of the positive control group. There were no significant differences between the transdermal treatment group and the positive control in terms of percentage inflammation (48.35%) and inflammation inhibition (45.75%). Similarly, the oral treatment group exhibited an inflammatory percentage of 63.44% and an inflammatory inhibition of 52.21%. It can be concluded that the transdermal patch formulation of melinjo leaf extract is effective as an anti-inflammatory treatment.